UPAYA PENINGKATAN PENGETAHUAN DAN SIKAP KADER DALAM PENCEGAHAN PEMBERIAN MAKANAN PRALAKTAL PADA BAYI 0-3 HARI - Fitriani, Iis Ria; Wisuda Andeka Marleni, Epti Yorita, (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
Infant Mortality in Bengkulu Province is still high, this can be prevented through breastfeeding as a staple food in infants 0-6 months without other complementary foods because breast milk boosts immune status for infants and thus can reduce mobility and mortality rates but exclusive ASI coverage still low, this is influenced by pralactal feeding in infants 0-3 days of birth. Research Objective to increase knowledge and attitude of cadre through training as promotion effort of prevention of pralactal food in 0-3 days old baby. Quasi pre and post test experiments with comparison groups. The study population were all cadres in Talang Tinggi Public Health Center, which were 50 people in Talang Tinggi Public Health Center, Seluma District with experimental group samples were cadres who were given training by using module and control group were cadres who were trained by using lecture and question and answer method. There is an average difference of attitude and knowledge before and after intervention in the cadres given training on prevention of pralactal food in infants 0-3 days. There is an effect of training on prevention efforts of pralactal feeding using modules with cadre attitude. Puskesmas should increase the promotion of prevention of pralactal food to change cadre attitude to support program exclusive breastfeeding.